Efficacy and safety of distal transradial access for coronary angiography and percutaneous coronary intervention: a meta-analysis - Yang, Qinyan; Wei, Xianli; Wu, Jianyu; Li, Chunlan; Qin, Yuechen; Zeng, Haijian; Qin, Mengtian; Zou, Yue; Zhang, Shiming; Liang, Weiming; Li, Jie (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThis meta-analysis aims to evaluate the efficacy and safety of dTRA for coronary angiography (CAG) and percutaneous coronary intervention (PCI) in comparison to cTRA.Materials and methodsFour databases (PubMed, Embase, Web of Science, and Cochrane Library) were searched from their inception to 13 April 2024 for studies comparing dTRA and cTRA in coronary diagnostic or interventional catheterization. The meta-analysis evaluated radial artery occlusion (RAO), procedure success, the success rate of catheter puncture, the success rate of a single attempt, hematoma occurrence, radial artery spasms, puncture site bleeding, puncture time, procedural time, the dosage of contrast medium, and hemostasis time.ResultsA total of 31 studies were included in the meta-analysis. Compared with cTRA, dTRA significantly reduced the incidence of RAO [odds ratio (OR) = 0.41, 95% CI: 0.34–0.50, P < 0.05], hematoma (OR = 0.67, 95% CI:0.56–0.80, P < 0.05), and shorter hemostasis time [weighted mean difference (WMD) = −0.43, 95% CI:−0.65 to −0.20, P < 0.05] but had a significantly lower procedure success rate (OR = 0.41, 95% CI: 0.30–0.56, P < 0.05), a lower catheter puncture success rate (OR = 0.44, 95% CI: 0.27–0.71, P < 0.05), and a longer puncture time (WMD = 0.60, 95% CI: 0.44–0.75, P < 0.05). No significant differences were observed between dTRA and cTRA in terms of the success rate of a single attempt, radial artery spasms, puncture site bleeding, procedural time, and dosage of contrast medium.ConclusionsOur results revealed that dTRA is a workable and safe method for cardiovascular interventional diagnostics and treatment. It significantly reduces the incidence of RAO and hematoma, as well as shortens hemostasis time following surgery.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024596238, PROSPERO (CRD42024596238).